1977
DOI: 10.1093/oxfordjournals.aje.a112360
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Persistence of Hepatitis B Surface Antigen and Antibody in a Melanesian Population1

Abstract: The population of Graciosa Bay, Santa Cruz, British Solomon Islands Protectorate, was tested for HBsAg and anti-HBs in 1973 and 1974. Both the antigen and antibody occurred more often in males, presumably due to a higher exposure rate. None of 28 infants under one year of age had antigen and only one of 50 individuals under two years (2%) did. The prevalence of antigenemia was higher in older children and did not decline with increasing age. This pattern is contrasted to that found in other populations which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
4
5
0
Order By: Relevance
“…The prevalence of HBsAg was highest in the 1O-29-year age group and declined in subjects over 30 years of age. The prevalence of anti-HBs declined in the fourth and subsequent decades of life, a trend that has been noted in other Pacific populations [17][18][19][20]. A higher proportion of males than females showed serological evidence of infection (78.2% vs. 70.7%), and the carrier rate was also higher in this group (12.7% vs. 7.2%).…”
Section: Methodssupporting
confidence: 57%
“…The prevalence of HBsAg was highest in the 1O-29-year age group and declined in subjects over 30 years of age. The prevalence of anti-HBs declined in the fourth and subsequent decades of life, a trend that has been noted in other Pacific populations [17][18][19][20]. A higher proportion of males than females showed serological evidence of infection (78.2% vs. 70.7%), and the carrier rate was also higher in this group (12.7% vs. 7.2%).…”
Section: Methodssupporting
confidence: 57%
“…Our study demonstrated a downward trend in HBsAg sero-prevalence from 2003–2018 ( Figure 2 , Table 1 ). This is in accordance with studies done in the Solomon Islands, which demonstrated a decline in HBsAg prevalence from 32% in 1977 [ 21 ] to 25.1% in 1999 [ 25 ] to 21.5% in 2007 [ 26 ]. Similarly, Fiji has seen a decline in prevalence from 17.9% in 1982 [ 22 ] to 0% in children, 5.6% in adolescents and 3.2% in adults in 2009 [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…The mean calculated HBsAg prevalence in this study is 23% (95% CI 23.0–24.0) and is similar to other studies found in the region before an expanded programme for immunization was introduced [ 5 , 21 , 22 , 23 , 24 ]; regional prevalence’s varied from 17.9% in Fiji [ 22 ], 32% in British Solomon Islands [ 21 ] and Kiribati [ 23 ], 42% in Tahiti [ 5 ] and 88% in Tonga [ 24 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies in Pacific populations have shown that the hepatitis B virus is endemic in the region (Austin, Maquire & Miles, 1974;Blumberg et al 1974;Mazzur & Jones, 1977;Gust, Lehmann & Dimitrakakis, 1979;Wong, Purcell & Rosen, 1979) and has revealed striking variations in the prevalence of infection and of chronic carrier rates amongst different groups (Gust, Dimitrakakis & Zimmet, 1978;Vitarana et al 1978). Numerous suggestions have been made to account for these observations, including inherited differences in response to infection, the effect of differences in child rearing and other social practices and differences in the virus itself.…”
Section: Introductionmentioning
confidence: 96%